Walking with individualized 3D-printed minimal footwear increases foot strength and produces subtle changes in unroll pattern - Allen, Alexandra; Pinheiro, Manuel; Schoenmaekers, Raf; D’Août, Kristiaan; Willems, Catherine (Frontiers in Ecology and Evolution, 2023)
We evaluated the biomechanics of walking while wearing bespoke, 3D-printed footwear, designed based on foot scans and previously established foot shape differences between habitually shod and barefoot populations.This 5-month follow-up study involved 66 subjects (38 intervention, 28 control; 34 females, 32 males). A 3D scanner was used to obtain foot shape, which was subsequently modified to yield a suitable instep and additional room in the forefoot and toe areas, to allow for potential shape changes of the foot. Shoes were manufactured using TPU laser sintering.Pre (T0) and post (T1) the intervention, plantar pressures were collected using a plantar pressure plate (3 trials per foot) and toe flexor strength (5 trials per foot) was measured using a dynamometer, for control and intervention groups. Plantar pressure peak patterns and center-of-pressure (CoP) timing was analysed using 2D and 1D Statistical Parametric Mapping, respectively. Toe strength changes were expressed in percent and per individual as: 100 x ((strength@T1strength@T0) / strength@T0).Peak pressure distribution did not differ between control and intervention populations, or between T0 and T1. Centre-of-pressure unroll differed between barefoot and shod conditions at T0 for the intervention group, which suggests that barefoot subjects' CoP moves faster in early and mid-stance than when shod. When barefoot, the intervention group at T1 showed a more lateral CoP in early This is a provisional file, not the final typeset article.stance and a more anterior CoP in late stance compared to T0. In the intervention group, toe strength increased significantly by 48.5% between T0 and T1.Overall, the results indicate that the bespoke, 3D-printed footwear did not significantly affect peak pressure distribution compared to barefoot walking. However, it influenced the center-of-pressure patterns during gait, particularly in the intervention group when walking barefoot. Additionally, the intervention led to a significant increase in toe strength. These findings contribute to our understanding of the biomechanical effects of customized 3D-printed footwear and highlight the potential benefits of such interventions in improving foot function and strength.